PERAN PENDIDIKAN DALAM MENGEMBANGKAN INTELEKTUAL SISWA MENURUT PERSPEKTIF SURAH AL-BAQARAH AYAT 31 - Ahmad Yusam Thobroni; Amalia Kholisha Nashihi; Rosa Amelia Basir; Mahesh Khusianand Aryana (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This study aims to explore the role of education in developing students' intellect from the perspective of Surah Al-Baqarah verse 31. Using a qualitative approach and library research methods, the study analyzes the interpretation of the verse and examines the concept of intellectual development in education. The findings reveal that Surah Al-Baqarah verse 31 emphasizes the urgency of education in optimizing human intellectual potential as one of the purposes of creation. Education should facilitate students in developing critical thinking, creativity, and problem-solving skills. Furthermore, the integration of spiritual values such as **tawhid** (monotheism), sincerity, patience, gratitude, and trustworthiness is crucial to ensure that intellectual development aligns with the purpose of human creation as servants of Allah SWT. The study recommends curriculum reform, the application of student-centered learning methods, improvement of the learning environment's quality, enhancement of teacher professionalism, and prioritization of the integration of spiritual values into the learning process. Thus, education can optimally contribute to the holistic development of students' intellect, encompassing both cognitive and spiritual aspects.